Pentahelix Partnership in The Development of Sustainable Tourism in The Bojonegoro District - Megawati, Suci; Falaq Al-Amin, M. Noer; Febrianti, Eni; Rahayu, Tjitjik (Indonesian Association for Public Administration (IAPA), 2024)
Collaboration for sustainable development is progressively gaining a dominating role in tourism. Sustainable tourism development focuses on the balanced development of society, the environment, and the economy as a whole; nevertheless, tourist development is not relevant when considering socio-cultural, economic, and local environmental demands, which are seen less beneficial for the local community. Pentahelix collaboration is advised to achieve theoretically and experimentally sustainable tourist development, but various research in Indonesia reveal that the responsibilities and activities of pentahelix stakeholders are not optimum and synergistic. The similar situation happened in Bojonegoro Regency's tourist development. As a result, the research intends to 1) make an academic contribution. Mapping and assessing tourist potential, as well as the overall tourism development plan in Bojonegoro Regency; 2) evaluating the pentahelix cooperation in Bojonegoro Regency Academics, Business, Community, Government, and Media are five (Five Elements) tourism subjects or stakeholders. The five aspects serve as markers for analyzing the pentahelix, which is managed and planned. Concerning the factors used to assess the effectiveness of sustainable tourism, there are five (five) indicators: ecological sustainability, economic sustainability, socio-cultural sustainability, political sustainability, and defense and security sustainability. This study resulted in the publishing of publications in recognized international journals and proceedings. This study's TKT begins at 2 and ends at 3